The Hidden Hand of Underwater Cultural Heritage : Submerged Intelligence for Global Omens - Pérez-Álvaro, Elena (Social Sciences E-Books Online, Collection 2025., 2025)
This book acts as a cautionary tale, urging society to proactively invest in forging a path towards the future by drawing upon the insights gleaned from the past. Underwater cultural heritage is not merely a collection of broken ruins on the ocean floor; it holds the potential to provide strategic intelligence into global security challenges and future uncertainties. By understanding and valuing the unknown force of underwater cultural heritage, we can anticipate and navigate potential future challenges, harnessing its hidden power to shape the course of history. See Less